Performance evaluation of zinc oxide varistor produced from powder under different spray drying conditions - Begum, Shahida; Karim, A.N. Mustafizul; Hashmi, M. S. J. (2006)
I-V characteristics, wattloss behavior and energy absorption capability etc. are the critical characteristics for performance evaluation of ZnO varistors. In the long processing steps of this electro-ceramic with a considerable number of contributing variables, the preparation of pressing grade electro-ceramic materials is very important. It demands powders with high degree of compositional and microstructural homogeneity, high purity and reliability, proper shape and proper size and distribution. This kind of ceramic powder can be generated by spray drying. Apart from affecting the physical properties of varistor discs, the powder characteristics influence the grain growth and microstructure which are anticipated to affect the electrical behavior of the discs. To investigate this, varistor powder was produced from standard slurry under different spray drying conditions in pilot scale. Feed flow rate, atomizing air pressure and outlet drying air temperature were considered as input variables and nominal voltage, wattloss, clamp ratio, non-linear co-efficient and energy absorption capability were considered as response. It was found that nominal voltage, wattloss and energy absorption capability was highly influenced by spray drying variables but no significant influence was observed on clamp ratio and nonlinear co-efficient for both the pre-breakdown and breakdown region. Not only high but consistent energy absorption capability was achieved by optimizing spray drying conditions. Thus optimization of spray drying variables could help securing desirable varistor characteristics and enhanced reliability of the electrical system.